Structure of the Kakinada cyclone of 6 November 1996 - SHARMA, R. V. (MAUSAM, 1999)
Radar is a very powerful tool in determining the position, speed and direction of movement, horizontal and vertical extent of the cyclone. Besides, the radar observations can also be expected to provide more vital information on the shape, size and behaviour of the eye of a cyclone. These features are very important input information for cyclone forecasting, especially in assessing the intensity of the cyclone. An effort has been made here to document the above features of a cyclone that struck the east Godavari coast in November 1996. The cyclone formed over central Bay of Bengal in the afternoon of 5 November 1996 and intensified into a severe cyclonic storm with a core of hurricane winds next day. The cyclone was tracked by Cyclone Detection Radar (CDR) Visakhapatnam from the initial stage of its formation till it crossed the coast near Kakinada. In this paper, the radar track of the cyclone over sea, along with the size. shape and behaviour of the eye as observed on radar have been discussed. The variation of other parameters like eyewall width, radius of maximum reflectivity and wall cloud height and relationship between eyewall width and eye diameter have also been discussed.